White Matter Abnormalities in Patients with Focal Cortical Dysplasia Revealed by Diffusion Tensor Imaging Analysis in a Voxelwise Approach - Fonseca, Viviane C.; Yasuda, Clarissa L.; Tedeschi, Guilherme G.; Betting, Luiz Eduardo; Cendes, Fernando (Frontiers in Neurology, 2012)
Background: Diffusion tensor imaging (DTI) allows the analysis of changes in microstructure, through the quantification of the spread and direction of water molecules in tissues. We used FA (fractional anisotropy) maps to compare the integrity of WM between patients and controls. The objective of the present study was to investigate WM abnormalities in patients with extratemporal epilepsy secondary to focal cortical dysplasia (FCD). Materials and Methods: We included 31 controls (12 women, 33.1± 9.6 years, mean ±SD) and 22 patients (11 women, 30.4 ± 10.0 years), recruited from our outpatient clinic. They had clinical and EEG diagnosis of frontal lobe epilepsy, secondary to FCD detected on MRI. Patients and controls underwent 3T MRI, including the DTI sequence, obtained in 32 directions and b value of 1000 s/mm2. To process the DTI we used the following softwares: MRIcroN and FSL/ TBSS (Tract-Based Spatial Statistics). We used a Threshold-Free Cluster Enhancement with significance at p<0.05, fully corrected for multiple comparisons across space. Results: Areas with FA reduction in patients were identified in both hemispheres, mainly in the frontal lobes, cingulum and forceps minor (p=0.014), caudate e anterior thalamic radiation (p=0.034), superior longitudinal fasciculus (p=0.044), uncinate fasciculus and inferior fronto-occipital fasciculus (p=0.042). Conclusion: Our results showed a widespread pattern of WM microstructural abnormalities extending beyond the main lesion seen on MRI (frontal lobe), which may be related to frequent seizures or to the extent of MRI-invisible portion of FCD.